Flora and fauna on commemorative coins of the National Bank of Ukraine - Totska, Olesia Leontiivna (My University, 2023)
Coins are one of the symbols of Ukrainian statehood. Images of their obverse and reverse help to form the national consciousness of Ukrainians, love for their native land and people, which is especially relevant in times of war. The purpose of this article is to review and classify commemorative coins of the National Bank of Ukraine from the "Flora and Fauna" series. The following classification features are defined: metal, coin denomination, minting quality category, image on the reverse. The research used data from the National Bank of Ukraine on numismatic products for 1995–2022; methods of analysis, classification, and generalization are applied. It was revealed that during 1995–2022, the National Bank of Ukraine issued 54 commemorative coins in the "Flora and Fauna" series: 31 – german silver, 23 – silver. The denomination of the coins was: 2 hryvnias – 26 coins, 5 hryvnias – 5 coins, 10 hryvnias – 23 coins. The minting quality categories of these coins were: uncirculated – 1, ordinary – 12, proof – 21, special uncirculated – 20. On the obverse of coins with representatives of flora and fauna, put into circulation until 2022, there is a small State Coat of Arms of Ukraine, inscriptions and the mint mark of the Banknote Printing and Minting Works of the National Bank of Ukraine in the frame of a wreath formed from images of certain types of flora and fauna. The reverse of the commemorative coins depicts representatives of flora and fauna, classified into the following groups: flora – 5, mammals – 8, birds – 5, insects – 2, fish – 3, crustaceans – 1. Several commemorative coins are dedicated to zoos, arboretum and steppe reserve.

Монети є одним із символів державності України. Зображення їх аверсу та реверсу допомагають формувати національну свідомість українців, любов до рідної землі та народу, що особливо актуально в час війни. Метою цієї статті є провести огляд і класифікацію пам’ятних монет Національного банку України із серії «Флора і фауна». Класифікаційними ознаками визначено: метал, номінал монети, категорію якості карбування, зображення на реверсі. У ході дослідження використано дані Національного банку України щодо нумізматичної продукції за 1995–2022 рр.; застосовано методи аналізу, класифікації, узагальнення. Виявлено, що упродовж 1995–2022 рр. Національний банк України випустив в обіг 54 пам’ятні монети в серії «Флора і фауна»: 31 – з нейзильберу, 23 – зі срібла. Номінал монет становив: 2 гривні – 26 монет, 5 гривень – 5 монет, 10 гривень – 23 монети. Категорії якості карбування цих монет були: анциркулейтед – 1, звичайна – 12, пруф – 21, спеціальний анциркулейтед – 20. На аверсі монет з представниками флори та фауни, введених в обіг до 2022 р., розміщено малий Державний Герб України, написи та логотип Банкнотно-монетного двору Національного банку України в обрамленні вінка, утвореного із зображень окремих видів флори та фауни. На реверсі пам’ятних монет відображено представників флори та фауни, яких класифіковано на такі групи: флора – 5, ссавці – 8, птахи – 5, комахи – 2, риби – 3, ракоподібні – 1. Декілька пам’ятних монет присвячені зоопаркам, дендропарку та степовому заповіднику.
Флора та фауна на пам’ятних монетах Національного банку України
Keywords: National Bank of Ukraine; commemorative coins; flora; fauna; coin obverse; coin reverse; Національний банк України; пам’ятні монети; флора; фауна; аверс монет; реверс монет